DEVOTIONAL OBJECTS IN A PERIFERICAL COLONIAL CITY (SANTIAGO DE CHILE 1598 – 1610; 1692 – 1710): AN INITIAL RESEARCH. - Schenke, Josefina (Revista de Historia Social y de las Mentalidades, 2011)
This paper sketches in a programmatic manner the main lines of an ongoing PHD research that tries to find out which images and objects of devotion existed, were in use or vanished in Santiago de Chile during two specific periods: 1598–1610/ 1692–1710. The research relates the variation in the presence of these objects to the devotional, social and urban contexts to which they belong. Grounded in a quantitative research of notarial and ecclesiastical sources, it aims to find every single object around which some special religious practice revolves: sculptures, prints, canvas boards, relics, medallions, rosaries and crosses. An estimate of the proportion in which each of this kinds of devotional elements occurs should afford us a better understanding of their organic combinations and their shared meanings. This paper faces the multiple aspects involved in this field of inquiry, as well as its status quaestionis and the methodological approaches of this research.
Keywords: image; relic; Santiago de Chile